2016
DOI: 10.5152/jtgga.2016.16144
|View full text |Cite
|
Sign up to set email alerts
|

Furan toxicity on testes and protective role of lycopene in diabetic rats

Abstract: Material and Methods35 male adult Wistar albino rats weighing 300 to 320 g were obtained from the Experimental Animal Laboratory of Çukurova University. The rats were inserted into special plasObjective: Furan (C 4 H 4 O) is a heat-induced food contaminant that is utilized as an industrial chemical agent. Lycopene is a natural substance that is produced by plants and tomatoes. We aimed to evaluate the toxicity of furan on testes and the protective effect of lycopene in diabetic rats. Material and Methods:Male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Subchronic furan and acrylamide exposure resulted in reduced seminal vesicle and testicular weight, along with reduced serum level of T, LH, FSH, and prolactin. 6,19,45 The bw is the most sensitive indicator of adverse effect of xenobiotics. It is notable that observing the bw is important for interpretation of reproductive effects of toxins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subchronic furan and acrylamide exposure resulted in reduced seminal vesicle and testicular weight, along with reduced serum level of T, LH, FSH, and prolactin. 6,19,45 The bw is the most sensitive indicator of adverse effect of xenobiotics. It is notable that observing the bw is important for interpretation of reproductive effects of toxins.…”
Section: Discussionmentioning
confidence: 99%
“…6,11,12 Adverse effect of furan has been tested for a variety of reproductive parameters, and prominent effects were reported in the reproductive systems of males and females. 11,[18][19][20] However, a study was conducted on Taiwanese boys whose mothers used contaminated (with polychlorinated biphenyls (PCBs) and furan) rice oil that resulted in smaller size of penis in comparison with age-matched control boys. 21 Similarly, Guo et al reported that sperms of prenatally exposed young men with PCBs and furan have abnormal sperm morphology, reduced sperm motility, and also reduced ability of sperm to enter hamster oocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Groups III and IV received gentamicin for 10 consecutive days, starting from the sixth day of the experiment till day 15. The doses of gentamicin 3,4 and lycopene [19][20][21] in this study were selected on the basis of the previous studies. The experiment was continued for 15 consecutive days.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…Cong et al (2015) and Chen et al (2016) who find eosinophilia in myocardial fibers and edema in connective tissue. Also, chemicals can cause histopathological changes in tissues, such as: liver (Bas, Pandır, & Kalender, 2016), kidneys (Pandir et al, 2016), and testes (Kara, Baş, & Pandır, 2016). Heart is one of the organs that is affected by chemical treatment.…”
Section: Stz-caused Dm Induces Oxidative Stress and Then Hyperglycemimentioning
confidence: 99%